Application of human-centered design practices in the agile requirements engineering process: a case study in a public company - Coutinho, Viviane de Oliveira Garcia; Souza, Maurício Ronny de Almeida; Freire, André Pimenta (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2024: Anais do XXIII Simpósio Brasileiro de Qualidade de Software, 2024)
The appropriate definition of software requirements is essential to the success of a project. Poorly defined or incomplete requirements can lead to errors and problems in the final system, resulting in rework, customer dissatisfaction and schedule delays. Agile requirements engineering faces challenges such as lack of documentation and ensuring the development team understands the customer’s needs. This challenge becomes even greater when the software is developed by a contracted company. This work presents an experience report on the application of human-centered design practices in the requirements engineering process in a government project. We observed (i) greater collaboration between team members, (ii) increase in the volume of ideas, (iii) early identification of problems in the project, (iv) generation of software with greater usability, (v) reduction of interpretation errors and lack of understanding of requirements, (vi) perception that the time invested in prototyping is compensated with the reduction of defects and rework.